Mentors, Muses, and Memories: Personal Narratives From Psychological Assessment. Issue 1 (2nd January 2016) - Waugh, Mark H.
Abstract : Development of professional identity occurs through the twin tracks of scientific and narrative learning. Mentoring plays a key role in this process. Didactically acquired knowledge can fade over time, but narrative learning may persist within professional skills, attitudes, and identity. As well, memories of key interactions with mentors endure, often carrying bits of generative wisdom. Stories of interactions with luminaries in the field of psychological assessment illustrate these dynamics and "lessons learned." Vignettes about George Welsh, Jane Loevinger, Molly Harrower, Sidney Blatt, and Paul Lerner are recalled. These are then explicated through an integration of early and contemporary scientific and professional literature, revealing their enduring relevance.